Biochemical Analysis of Different Implant-Abutment Connections in the Prosthetic Rehabilitation of the Anterior Maxilla: a Finite Element Study - Corrêa, Cássia Bellotto; Margonar, Rogério; Noritomi, Pedro Yoshito; Pigossi, Suzane Cristina; Vaz, Luís Geraldo (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Purpose: This study aimed to evaluate, through 3D finite elements method, the biomechanical behaviour of three different types of prosthetic connections (external hexagon (EH), internal hexagon (IH) and morse taper (MT)) in implant-supported fixed partial dentures (ISFPD) placed in the anterior region of the maxilla. Methods: A 3-dimensional (3D) anatomical model of the anterior maxilla was constructed using a computed tomography database. The implants were positioned in the lateral incisor positions and pontics in the central incisor positions simulating an ISFPD with four cemented elements. The prosthetic rehabilitation was made with three connections implant systems including MT, EH and IH. The applied load of 150N was distributed at the center of the palatal surface of each tooth, with an angle of 45° related to the tooth long axis. The distribution of strain/stress was analyzed in all groups. Results: The implant connection design influences the distribution and intensity of stress/strain on the prosthesis/implant system. The EH connection promotes less displacement of the prosthetic structure in the case studied; however, the abutment screw of this connection receives the most of the von Mises stress of the system. The MT connection showed small values of von Mises stress in the screw in comparison to EH and IH connections type. Conclusions: The MT abutment seems to be more advantageous than the EH and IH connections concerning stress distribution in our study model.